Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Solving - Choirudin Choirudin; M. Saidun Anwar; Nur Khabibah (Universitas Nusa Cendana, 2021)
The purpose of this study is to create and develop teaching materials in the form of Students’ Worksheet (LKPD) Based on Problem Solving in Social Arithmetic Materials. Problem solving steps are used in LKPD, according to the steps according to Polya, namely: (1) understanding the problem; (2) planning; (3) implement the plan; (4) look back or check again. This type of research is Research and Development (RND), using development steps according to Borg & Gall which has been transformed by Sugiyono. The development steps are limited to seven steps. Among them; potential and problems, gathering information, product design, product validation, product improvements, product trials, product revisions. The final percentage of design expert validation is 90%, with very valid categories, 80% with valid categories from material experts, and 95% with very valid categories from linguists. As well as the results of questionnaire responses students get an average of 3.1 with interesting criteria. So it can be concluded that LKPD is feasible to be developed.